Predictive modeling with SAS Enterprise Miner : practical solutions for business applications - Sarma, Kattamuri S. (SAS Institute, 2017)
Written for business analysts, data scientists, statisticians, students, predictive modelers, and data miners, this comprehensive text provides examples that will strengthen your understanding of the essential concepts and methods of predictive modeling. --